Indirect systolic blood pressure measurements in cats - Wlosinska, Julia (2022)
Blood pressure (BP) measurements in cats are performed regularly in the clinical setting. As cats are easily stressed by their surroundings, the so-called white coat effect can easily influence the measurements obtained in the clinical environment. For some animals this could lead to a false diagnosis of hypertension. On the other hand, true hypertension that is not diagnosed (and therefore not treated) might eventually lead to damage of target organs. Therefore, reliable BP measurements are a very important part of the clinical handling of feline patients. In order to minimize anxiety-induced rises in blood pressure, it is essential to perform blood pressure measurements in cats using a stress-reduced measurement process. This includes, amongst others, having the owner present, using a quiet location with dimmed lights as well as allowing the cat to acclimatize to its surroundings before beginning the measurements. Following a stress-reduced blood pressure protocol might enable the cat to relax and eventually reach a lower plateau in its blood pressure measurement results. The primary purpose of this study was to examine whether a prolonged measurement time can allow the cat to acclimatize to a clinical environment to such an extent that it lowers the cat’s stress level and, in turn, generates a more distinct plateau of lower BP measurement results. Another purpose was to examine the owner’s perception of performing a BP measurement on their cat themselves when using an automated indirect BP measuring device. A total of 37 cats were included in the study. Twenty-six cats were subject to a prolonged measurement procedure. A clear downward trend was seen in recorded BP for most of the cats during the prolonged measurement time. During the prolonged measurement time, a median number of five additional BP measurements were performed. Most owners in this study reported it to be easy to perform BP measurements on their cats. The study concludes that a prolonged BP measurement time will in general result in lower BP values. By prolonging the BP measurement time, the white coat effect can be reduced in some cats. According to this study, a prolonged BP measurement time should be recommended for cats with initially high BP measurement results. The study also concludes that it is beneficial to allow the cat owner to perform BP measurements on their animal themselves, if and when possible.